Therapeutic modulation of neuroinflammatory and apoptotic pathways by PEPITEM in an EAE model of multiple sclerosis - Alassiri, Mohammed (Trends in Immunotherapy, 2024)
Objective: To examine the therapeutic effects of PEPITEM on neuroinflammatory and apoptotic pathways in an Experimental Autoimmune Encephalomyelitis (EAE) model of Multiple Sclerosis (MS), focusing on the modulation of key biomarkers: SIRT1, NRF2, NF-κB p65, Bax, and Bcl2. Methods: We utilized a controlled experimental design involving five groups of female C57BL/6 mice, aged 9–12 months to assess the effects of PEPITEM administered therapeutically and prophylactically. Groups included a normal healthy mice group (G1), an EAE-induced group receiving scrambled peptide therapeutically (post-induction) (G2), an EAE-induced group treated with PEPITEM therapeutically (G3), and an EAE-induced group given scrambled peptide (G4) prophylactically or, an EAE-induced group treated with PEPITEM prophylactically (G5). Following induction and PEPITEM treatment, weight and EAE scores were compared among the designated groups. Additionally, spinal cord tissues were harvested for protein lysate preparation and Western blot analysis quantified the expression levels of the selected biomarkers. Results: Analysis of the weight and EAE scores reveals that G3 and G5 exhibit trends toward recovery, potentially indicating the effectiveness of the treatment. Moreover, PEPITEM treatment significantly upregulated the expression of SIRT1 and NRF2, suggesting an enhanced neuroprotective and antioxidant response. Conversely, NF-κB p65 and Bax levels were notably decreased, indicating a suppression of inflammatory and apoptotic pathways. Additionally, Bcl2 expression was significantly increased, highlighting a shift toward cell survival mechanisms. Conclusion: Our findings demonstrate that PEPITEM exerts a multifaceted therapeutic effect in the EAE model of MS by mitigating the symptoms of EAE as evidenced by modulating crucial biomarkers involved in neuroprotection, inflammation, and apoptosis. The significant alterations in the expression of the biomarkers highlight the potential of PEPITEM as a promising therapeutic agent for MS, offering insights into its mechanism of action and paving the way for future clinical investigations.